Effectiveness of photodynamic therapy of a patient with early central lung cancer and cystic fibrosis - E. S. Borzenko; I. V. Reshetov; A. S. Fatyanova; K. V. Ogdanskaya; M. M. Gafarov; Yu. S. Romanko (Biomedical Photonics)
The authors describe a clinical observation with full clinical effect after multi-course photodynamic therapy of a patient with central lung cancer and cystic fibrosis using Photoditazine. Photoditazine was administered intravenously at a dose of 0.8 mg/kg 2 hours before the irradiation session. Irradiation parameters: power density – 150 mW/cm2, energy density – 200 J/cm2. In total, 3 courses of photodynamic therapy were performed. As a result of the treatment, a complete regression of the tumor was noted. The patient has been under dynamic observation for 2 years after treatment, no relapse was observed.